2002
DOI: 10.1590/s1415-47572002000100013
|View full text |Cite
|
Sign up to set email alerts
|

Variability among inbred lines and RFLP mapping of sunflower isozymes

Abstract: Eight isozyme systems were used in this study: acid phosphatase (ACP), alcohol dehydrogenase (ADH), esterase (EST), glutamate dehydrogenase (GDH), malate dehydrogenase (MDH), phosphoglucoisomerase (PGI), 6-phosphogluconate dehydrogenase (PGD), and phosphoglucomutase (PGM). The polymorphism of these enzyme systems was studied in 25 elite inbred lines. A total of 19 loci were identified, but only eight of them were polymorphic in the germplasm tested. The polymorphic index for the eight informative markers range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Few molecular markers like simple sequence repeats (SSRs) (Iqbal et al, 2010;Garayalde et al, 2011), random amplified polymorphic DNA (RAPD) (Isaacs et al, 2003;Wangsomnuk et al, 2011a), target region amplification polymorphism (TRAP) (Yue et al, 2009;Yue et al, 2010), restriction fragment length polymorphism (RFLP) (Carrera et al, 2002), amplified fragment length polymorphism (AFLP) (Rachid et al, 2004;Dong et al, 2007;Vos et al, 1995) and inter simple sequence repeats (ISSRs) (Wangsomnuk et al, 2011b) have widely applied for marker-assisted selection (MAS), genomic evolution and used in some oilseed crops breeding research (SztubaSolińska, 2005). Mostly, genetic studies have separate principles and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Few molecular markers like simple sequence repeats (SSRs) (Iqbal et al, 2010;Garayalde et al, 2011), random amplified polymorphic DNA (RAPD) (Isaacs et al, 2003;Wangsomnuk et al, 2011a), target region amplification polymorphism (TRAP) (Yue et al, 2009;Yue et al, 2010), restriction fragment length polymorphism (RFLP) (Carrera et al, 2002), amplified fragment length polymorphism (AFLP) (Rachid et al, 2004;Dong et al, 2007;Vos et al, 1995) and inter simple sequence repeats (ISSRs) (Wangsomnuk et al, 2011b) have widely applied for marker-assisted selection (MAS), genomic evolution and used in some oilseed crops breeding research (SztubaSolińska, 2005). Mostly, genetic studies have separate principles and functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a major source of genes for Verticillium wilt (Verticillium dahliae), downy mildew (Plasmopara halstedii) and rust (Puccinia helianthii) resistance, tolerance to sunflower moth (Homoeosoma electellum) and genetic improvement of cultivated sunflower (Jan and Seiler, 2007). Phenotypic genetic markers are useful for marker-assisted selection in the field and despite intense research, only a few have been identified in sunflower and its relatives (Gentzbittel et al, 1999;Gedil et al, 2001 andCarrera et al, 2002). Most studies in this species refer to hybridization with H. annuus (Heiser, 1947;Rieseberg et al, 1995;Rieseberg et al, 1999;Buerkle andRieseberg, 2001 andPoverene et al, 2004) but scanty information are available about specific traits inheritance.…”
Section: Introductionmentioning
confidence: 99%